Validity and Reliability of Turkish Version of the Individual Work Performance Questionnaire - Nagihan Köroğlu; Havva Öztürk (Association of Nurse Managers, 2021)
Aim: The purpose of the current study was to perform Turkish validity and reliability tests of the 'Individual Work Performance Questionnaire'. Method: This methodological study was undertaken with 309 nurses who worked at two public hospitals located in the Black Sea Region. The data were collected using the 'Information Request Form' and 'Individual Work Performance Questionnaire'. Analyses of language and content validity, construct validity, and reliability was performed. Results: The average age of the participating women was 28.77+-6.25 years, average professional experience was 6.73+-5.76 years, 85.4% of the participants were female (n=264), 54% were single (n=167), and 60.2% had undergraduate degrees (n=186). It was seen that the content validity index of the questionnaire was.96. The confirmatory factor analysis results were; X2/sd= 2.55, RMSEA=.071, GFI=.92, CFI=.92, NFI=.88, IFI=.92 and TLI=.90. The total questionnaire Cronbach alpha coefficient was,80. Conclusion: As a result, the 'Individual Work Performance Questionnaire' made of 14 items used to determine nurses' work performance levels was valid and reliable. Nurses' work performance levels could be measured correctly and consistently.